2009
DOI: 10.1111/j.1365-2044.2009.06065.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of patient safety incidents submitted from Critical Care Units in England & Wales to the UK National Patient Safety Agency*

Abstract: SummaryWe reviewed and classified all patient safety incidents submitted from critical care units in England and Wales to the National Patient Safety Agency for the first quarter of 2008. A total of 6649 incidents were submitted from 141 organisations (median (range) 23 (1–268 incidents)); 786 were unrelated to the critical care episode and 248 were repeat entries. Of the remaining 5615 incidents, 1726 occurred in neonates or babies, 1298 were associated with temporary harm, 15 with permanent harm and 59 requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
9
1
1
Order By: Relevance
“…All prescription charts are checked daily by a dedicated intensive care pharmacist to minimize prescription errors. This might explain why in this study - in contrast to other studies [11,16,17] - medication errors were not the commonest reported type of CI.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…All prescription charts are checked daily by a dedicated intensive care pharmacist to minimize prescription errors. This might explain why in this study - in contrast to other studies [11,16,17] - medication errors were not the commonest reported type of CI.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, discussion of and feedback on CIs help to promote a culture of safety and learning [10]. A growing body of studies on CI reporting has been published in recent years, but only a few publications analyze large data sets [11] or longer observation periods. Many reports refer to CI reporting in anesthesia [12], but little evidence about the distribution of CIs in intensive care is available.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this is frequently not recognised 10–12. Several factors have been identified as contributing to the failure to recognise clinical deterioration, including: not taking vital signs, not recognising physiological deterioration in those vital signs, not communicating concern and not responding appropriately where physiological deterioration has been identified 13 14…”
Section: Introductionmentioning
confidence: 99%
“…While it is acknowledged that adverse events are common, methodological heterogeneity between studies limits our ability to quantify prevalence across different healthcare settings. In critical care, patients who die have higher rates of adverse events than those who survive 22. In prehospital care, adverse events, such as the failure to recognise severity of illness, are common in children who subsequently die in a paediatric intensive care unit 23…”
Section: Risk Managementmentioning
confidence: 99%